PERANAN ZAT PENGATUR TUMBUH ALAMI DALAM INDUKSI PEMBUNGAAN DAN PRODUKSI BERBAGAI VARIETAS TANAMAN CABAI (Capsicum annum L.) - Alvriado Igo Fransiscus Siahaan; Sukendah Sukendah; Sutini Sutini (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Cayenne pepper (Capsicum annum L.) is a vegetable commodity that has received a lot of attention because it has a high economic value and the need for chili continues to increase every year in line with the increasing population and the development of industries that need chili as raw materials. One of the efforts to increase flowering induction and chilli production is by using natural plant growth from young corn and different types of chili varieties. This research was conducted from February to July 2019, which was carried out in the Karangploso farmer group land, East Java. This research is a factorial experiment that uses 2 factors compiled using a Completely Randomized Design (CRD). The first factor is a natural plant growth (with consentration 0, 3, 6, and 9, ml/L) and the second factor is a variety of chili varieties (Maruti, Santika, and Jalapeno). The results of the study showed that there were interactions on the parameters of the number of leaves, number of flowers, number of chilies, and weight of chili per plant. natural growth regulators of young corn extract affect plant growth and production on the variable number of leaves, number of flowers, number of chilies, and weight of chili per plant with different results, as well as the second factor, the type of Maruti variety shows the best results on the parameter number of leaves, and the number of flowers, Santika varieties showed the best results on the parameters of the number of flowers and the number of fruit per plant, while the Jalapeno variety did not show a significant effect.